HASIL BELAJAR KOGNITIF IPA FISIKA SISWA DALAM PEMBELAJARAN KOOPERATIF FORMASI REGU TEMBAK DI SMP NEGERI 34 PEKANBARU - Eka Norbaizura; Nur Islami; Mitri Irianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research aims to describe and differentiate the cognitive learning physics through the implementation of a firing line strategies in cooperative learning for the material of optical instruments in the class of VIII SMPN 34 Pekanbaru. Population in this research is all of VIII classes with 199 students. Meanwhile the samples are 40 students in VIII2 as control class and 39 students in VIII3 as experiment class. The instrument of data collection in this study is a cognitive performance test which consists of 25 multiple choice items. Analysis of the data in this study was a descriptive analysis that was used to determine the performance of the physics cognitive learning through the criteria of absorption and effectiveness of learning. The inferential analysis was used to differentiate a cognitive learning considerably using independent samples t-test of SPSS 20 program. The analysis data shows: the average absorption of the class is 83.79% of the higher in category, and declared effective learning efficiently. The value of t tests is t (69.1) = 2,000, p = 0.049 means p <0.05, then Ho is rejected. Which means that there are differences in cognitive test result between students in experiment class that taught using cooperative learning firing line strategies and control class that uses conventional learning with a level of 95%. It can therefore be concluded that the implementation of the firing line strategy can be used as an alternative in the learning process in the classroom VIII SMPN 34 Pekanbaru.Key words : Cognitive result test, the firing line strategy, optical instruments.2